Role of hyperoxygenation on surgical site wound infection: a randomised case control study - Rao G., Samba Siva; Suggala, Kiran Kumar (International Surgery Journal, 2019)
Background: The aim of this study was to assess the influence of hyperoxygenation on surgical site wound infections. Methods: Using prospective randomized study, conducted from January 2018 to December 2018 at Mamata Medical College and General hospital, Khammam. This study includes 100 patients who were going for elective surgery at various divisions of Department of surgery. Patients were assigned randomly to an oxygen/air mixture with a faction of inspiration (FiO2) of 30% (n=50) and 60% (n=50). Administration was started after induction of anaesthesia and maintained for 3hours after surgery. Results: Surgical site infection was recorded in 5 patients (2 of 50, 10%) in the hyperoxygenation group and 11 patients (11 of 50, 22%) in the control group (p<0.05). Time of hospitalization was 5±3 days in the hyperoxygenation group and 9±4 days in the control group (p<0.05). Conclusions: Hyperoxygenation was associated with a reduction in surgical site infection. It also decreases the duration of hospital stay and decreases economic burden.